Analysis of Water Quality and Pollution Index at Karangantu Fishing Port Area, Banten - Roza Ruspita; Atika Aulia (Jurnal Akademika Kimia, 2022)
Karangantu fishing port symbolizes the rapid fishing industry in Serang, Banten. So many activities in the Karangantu fishing port area, such as a place for landing fisherman’s boats, shipping fish catches, and tourism object. These activities may impact the water quality. This research aims to analyze the water quality and pollution index in Karangantu fishing port. The water sample was carried out by purposive sampling in three stations around the Karangantu fishing port area: the estuary area, the fish auction, and the dock. Twelve parameters were analyzed: temperature, turbidity, transparency, TDS, TSS, pH, DO, COD, nitrate, cadmium, lead, and total coliforms. The water quality analysis result was compared by Class III water classification based on PP RI Nomor 82. Water quality was determined by the pollution index based on the minister of environment decree No. 115/2003. The result indicates that the estuary area is polluted, with a PIj score of 6.35; the fish auction and the dock f are in the moderately polluted categories, with PIj scores of 4.99 and 3.90. The worse pollution can be prevented by raising public awareness about the importance of clean water and providing waste management facilities.